2011
DOI: 10.1109/tmi.2010.2076827
|View full text |Cite
|
Sign up to set email alerts
|

PET Image Reconstruction Using Information Theoretic Anatomical Priors

Abstract: We describe a nonparametric framework for incorporating information from co-registered anatomical images into positron emission tomographic (PET) image reconstruction through priors based on information theoretic similarity measures. We compare and evaluate the use of mutual information (MI) and joint entropy (JE) between feature vectors extracted from the anatomical and PET images as priors in PET reconstruction. Scale-space theory provides a framework for the analysis of images at different levels of detail,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 24 publications
(21 reference statements)
1
81
0
Order By: Relevance
“…A recent review on using anatomical prior information for PET image reconstruction can be found in [2]. Among different regularization methods [3]–[8], [10]–[13], the Bowsher method [9], which adaptively chooses neighboring pixels for each pixel in the image estimate using information from a prior image, was found to utilize anatomical prior information better than others in terms of performance and computational complexity [16]. The nonlocal regularization [17] can incorporate anatomical weights through a methodology similar to the neighborhood selection in the Bowsher method [14], [15] to improve emission reconstruction [18]–[20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on using anatomical prior information for PET image reconstruction can be found in [2]. Among different regularization methods [3]–[8], [10]–[13], the Bowsher method [9], which adaptively chooses neighboring pixels for each pixel in the image estimate using information from a prior image, was found to utilize anatomical prior information better than others in terms of performance and computational complexity [16]. The nonlocal regularization [17] can incorporate anatomical weights through a methodology similar to the neighborhood selection in the Bowsher method [14], [15] to improve emission reconstruction [18]–[20].…”
Section: Introductionmentioning
confidence: 99%
“…28 In fact, anatomy guided PET reconstruction allows concurrent improvements in both the effective spatial resolution and signal-to-noise ratios in the reconstructed images. Nonetheless, a number of simplifying assumptions are commonly made (e.g., uniformity in radiopharmaceutical uptake within anatomic labels): to this end, more sophisticated approaches [29][30][31][32][33][34] have been investigated, though they are often seen to introduce a number of additional parameters to be further fine-tuned for particular tasks of interest. This approach thus remains an open area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach of using the mDixon imaging technique with its inherent segmentation into watery and fatty compartments obviates additional image processing and may therefore be preferable. One standard approach to incorporate prior anatomic information into the reconstruction algorithm is technically motivated by the Bayesian framework, in which maximization of the logarithm of the posterior probability directly reveals the prior-here, the lower probability of tracer accumulation in fat tissue-as an additive penalty term (15,16,28). Typically, these schemes seek to establish contiguous regions of uniform uptake in the PET image that correspond to edge-separated regions in the MR or CT image, for instance, minimum cross-entropy reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Augmentation of standard iterative reconstruction algorithms (11,12) with penalty and regularization terms to enforce desired image characteristics such as regional smoothness (13), or, equivalently, Bayesian motivated reconstruction techniques (14) using appropriate priors, has been proposed for this purpose. The insight that the spatial distribution of a PET tracer is constrained not only by the underlying physiology but also to some extent by anatomy has led to penalization approaches that use the anatomic information gained from CT or MR images, again with the rationale of achieving spatial correlation of continuities and discontinuities between metabolic and anatomic images (15)(16)(17). In this work, we incorporated into the PET reconstruction algorithm a soft constraint that down-weighs PET image values in regions of tissue types in which tracer uptake is not expected, in favor of surrounding regions.…”
mentioning
confidence: 99%